SPECIAL ASPECTS OF EVALUATING THE CRACKING RESISTANCE OF BEAMS WITH PRESTRESSED REINFORCEMENT IN THE PROGRAM OF THEIR BENCH TESTS - Sim, Alexander; Belutsky, Igor (Journal of Applied Engineering Science, 2020)
This article provides information on the “Bypass of Khabarovsk city” road and all its associated transport infrastructure facilities. A method for evaluating the crack resistance of beams under bench test conditions is given. Based on the provisions of the theory of bending, expressions are presented for determining stresses for crack resistance
Keywords: bending of the beam; stress; relative deformation; testing on the ground; prestressed concrete beam; transportation; resistivity; evaluation; crack